Pelatihan Branding dan Kemasan Produk Menarik dengan Modal Minim Bagi UMKM Desa Sirnajaya - Asral .; Indra Permana; Sri Wahyuningsih; Supartono . (CV. ITTC INDONESIA, 2026)
This community service program aimed to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Sirnajaya Village to develop attractive product branding and packaging with limited capital. The main challenges faced by participants were a lack of understanding of brand identity and the perception that high-quality packaging requires high costs. The program applied a participatory and need-based approach through several stages: needs analysis, program design, implementation, and evaluation. The training materials included fundamental concepts of branding, low-cost promotional strategies, aesthetic and functional packaging design, and efficient material management. The results showed improvement in participants’ ability to apply simple branding strategies and create appealing yet economical packaging. Moreover, the activity increased participants’ motivation and confidence to develop more competitive and sustainable local products at the village level.